The Development of Adaptive E-Scaffolding to Support the Academic Diversity of High School Students on Mechanical Waves Material - Sahal Fawaiz; Supriyono Koes-H; Hari Wisodo (Universitas Lambung Mangkurat, 2024)
Waves are an abstract concept frequently challenging for students to grasp, as it is believed that only talented students can master it. Moreover, upon entering the classroom, each student possesses a unique understanding. Differentiated learning is suggested as a solution to manage the diversity of students in the classroom. This study aims to develop adaptive e-scaffolding for the Moodle LMS. This study design was the research and development using Analyze, Design, Develop, Implement, and Evaluate (ADDIE) model. Variable levels of scaffolding are incorporated into adaptive e-scaffolding by student abilities. The validation conducted by three experts in physics education and educational technology yielded a score of 3.78 and deemed adaptive e-scaffolding valid. The implementation outcomes show that the adaptive e-scaffolding achieves an average readability percentage of 79.2%, and the highest score was obtained in the feedback category. In summary, implementing adaptive learning technologies, such as e-scaffolding, can enhance students' engagement with learning materials and assist teachers in addressing classroom diversity. Teachers, e-learning developers, and other professionals in the field of education must give due consideration to how technology enables adaptive learning strategies.